2016
DOI: 10.1016/j.ijid.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of interferon-lambda 4 ss469415590 with the hepatitis C virus treatment response and its comparison with interleukin 28b polymorphisms in predicting a sustained virological response: a meta-analysis

Abstract: IFNL4 ss469415590 is significantly associated with SVR in HCV genotype 1 patients, irrespective of race; there is a tendency towards an association in HCV genotype 2/3 patients. Comparable to IL28B, IFNL4 is correlated with natural viral clearance and HCV susceptibility, additionally IFNL4 ss469415590 has a slightly higher predictive performance over IL28B polymorphisms in regard to SVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…RBV, which is routinely used to treat HCV infection, and favipiravir, which is one of the therapeutic options for COVID‐19, actually have very similar mechanisms of action 8 : They bind RNA‐dependent RNA polymerase, which is the key enzyme in the life cycle of many RNA viruses, including SARS‐CoV‐2. In RBV‐treated HCV patients, carriers of IFNL3 rs8099917 and IFNL4 rs12979860 showed higher risk of nonresponse to treatment, and more frequent development of chronic infection, 9 while the presence of IFNL4 rs368234815 TT/TT genotype was frequently associated with better response to therapy 10 . In addition, it was observed that the effect of genetic polymorphism may depend on the HCV subtype: rapid response to antiviral therapy involving RBV in HCV subtypes 1a and 1b was associated with the presence of several single nucleotide polymorphisms (SNPs), most importantly rs1298027533 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RBV, which is routinely used to treat HCV infection, and favipiravir, which is one of the therapeutic options for COVID‐19, actually have very similar mechanisms of action 8 : They bind RNA‐dependent RNA polymerase, which is the key enzyme in the life cycle of many RNA viruses, including SARS‐CoV‐2. In RBV‐treated HCV patients, carriers of IFNL3 rs8099917 and IFNL4 rs12979860 showed higher risk of nonresponse to treatment, and more frequent development of chronic infection, 9 while the presence of IFNL4 rs368234815 TT/TT genotype was frequently associated with better response to therapy 10 . In addition, it was observed that the effect of genetic polymorphism may depend on the HCV subtype: rapid response to antiviral therapy involving RBV in HCV subtypes 1a and 1b was associated with the presence of several single nucleotide polymorphisms (SNPs), most importantly rs1298027533 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In RBV-treated HCV patients, carriers of IFNL3 rs8099917 and IFNL4 rs12979860 showed higher risk of nonresponse to treatment, and more frequent development of chronic infection, 9 while the presence of IFNL4 rs368234815 TT/ TT genotype was frequently associated with better response to therapy. 10 In addition, it was observed that the effect of genetic polymorphism may depend on the HCV subtype: rapid response to antiviral therapy involving RBV in HCV subtypes 1a and 1b was associated with the presence of several single nucleotide polymorphisms (SNPs), most importantly rs1298027533. 10 Given all the similarities between HCV and COVID-19, it would be interesting to examine the potential role of IFNLs polymorphisms in SARS-CoV-2 infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although on-treatment predictors are more significantly associated with therapeutic success,39 the viral genotype and the rs368234815 IFNL4 SNP are considered the most powerful pretreatment predictors of response to PEG-IFN/RBV therapy 40…”
Section: Hcv Pharmacogenomicsmentioning
confidence: 99%
“…36 Among these two markers, we chose the one with the most extensive validation: many more studies (including a higher number of participants) cover IFNL3 polymorphisms than IFNL4. 6,37 The usefulness of the IFNL3 genotype as an SVR predictor in patients receiving IFN-based therapy (either because of lack of access to DAAs or contraindications to receive them) was also acknowledged in several practice guidelines across the world. 20,38e43 Triplex HRM: IFNL3, ABCB11, RNF7 in CHC Second, we selected genetic markers that provide prognostic information not only on the probability of SVR, but also on that of disease progression (fibrosis).…”
Section: Choice Of Ifnl3 Polymorphism Over Ifnl4mentioning
confidence: 99%